Modeling epistemic distance: the Croatian l–participle - Stanojević, Mateusz-Milan (Array, 2011)
The Croatian l–participle (inflected for gender and number) is used to form the Perfect Tense (on je otišao), the Pluperfect Tense (on je bio otišao), the Present and Past Conditional (on bi otišao, on bi bio otišao), Future II in dependent clauses (ako budeš otišao), and the Optative (živio). Traditional Croatian grammars (Barić et al. 1990 ; Katičić 1991) claim that the l–participle symbolically expresses gotovost ’finiteness’, i.e. the fact that the action has been completed before some point in time, but that it has ramifications for the point of speaking (cf. e.g. Katičić 1986:203–217 ; Katičić 1991:45–46). This account is not satisfactory, because it cannot coherently account for the use of l–participle in all the l–participle constructions. We claim that the l–participle expresses epistemic distance, which is related to the l–participle being a viewpoint operator (DeLancey 1981) signaling retrospectivity, and it referring to a property of the first participant in an action chain (Langacker 1987), implying non–permanence of the characteristic attributed by it. Such an analysis of the Croatian l–participle fits in with: (1) the constructions it is used in ; (2) its structural characteristics in Croatian (e.g. possible omission of the auxiliary in 3rd person singular in the Perfect Tense) ; (3) the meanings of the Croatian Present Tense, Aorist and the n–participle ; and (4) cross–Slavic evidence. Ultimately, this view suggests that the tense system in Croatian is aspect–based.